Asymmetric Organocatalytic Cascade Michael/Hemiketalization/Retro‐Aldol Reaction of 2‐[(E)‐2‐Nitrovinyl]phenols with 2, 4‐Dioxo‐4‐arylbutanoates: A Convenient Access to Chiral α‐Keto Esters. Issue 13 (28th August 2013) - Liu, Yunting; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract An unprecedented organocatalytic enantioselective cascade Michael/hemiketalization/retro‐aldol reaction of 2‐[(E)‐2‐nitrovinyl]phenols and 2, 4‐dioxo‐4‐arylbutanoates is described. With a bifunctional squaramide catalyst incorporating (1R, 2R)‐1, 2‐diphenylethane‐1, 2‐diamine, the reactions afford products in 75–99% yields with 80–98% ee. This process provides an enantioselective pathway for the synthesis of chiral α‐keto esters, precursors of 3‐arylproline derivatives, δ‐amino α‐keto acids or cyclic α‐keto lactams. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>